PERAN KIAI DALAM PEMBINAAN AKHLAK SANTRI DI PONDOK PESANTREN - Tatang Luqmanul Hakim; Iwan Sopwandin (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The kiai as a charismatic figure has a very large influence and role in fostering the morals of the santri, apart from being a central figure, the kiai through his in-depth knowledge can also determine the education system in the pesantren. The knowledge of a kiai usually has a very strong and well-maintained sanad to the main owner. Scientific Sanad is an intellectual tradition that has been attached to Islamic boarding schools for a long time, through this the authenticity and truth of knowledge is maintained. Sanad within the scope of Islamic boarding schools has a meaning as a link between knowledge between teachers and students. The research method used is field-based qualitative research. The data sources used are primary data sources and secondary data sources with data collection techniques through observation, interviews and documentation. While data analysis is done through the process of data reduction, data presentation and data verification. The results showed that: 1) The scientific Sanad of the Manarul Huda Ciamis Islamic Boarding School has similarities with the Miftahul Huda Manonjaya Islamic Boarding School, this can be seen from the similarity of vision and the basic handbook which contains important prayers given to new students which are useful as a basic guide in preparation for facing community life; 2) The actuality of the santri's morals can be categorized as good by having a scope commonly called the values of moral education which consists of morals to Allah SWT, morals to the kiai, morals to administrators, morals to oneself, morals to fellow human beings, morals to nature; 3) The role of the Kiai's scientific sanad in the moral development process consists of three roles, namely: first, the role of the kiai as a caretaker; Second, the role of kiai as educators; Third, the role of the kiai as a preacher